2017
DOI: 10.1007/s13197-017-2795-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of whole and skim dried milk powders

Abstract: The lack of updated knowledge about the physical properties of milk powders aimed us to evaluate selected physical properties (water activity, particle size, density, flowability, solubility and colour) of eleven skim and whole milk powders produced in Europe. These physical properties are crucial both for the management of milk powder during the final steps of the drying process, and for their use as food ingredients. In general, except for the values of water activity, the physical properties of skim and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
78
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 39 publications
10
78
1
1
Order By: Relevance
“…The a* values were negative across all samples with significantly (p ≤ 0.001) higher values observed for SMP than FFWMP and IMF samples across all treatments with the highest a* value observed in the SMP stored at 37 • C (-5.83). As expected, significantly (p ≤ 0.001) higher b* (yellowness) values were observed in FFWMP samples, due to the increased fat content [27]. Increased b* values (blue-to-yellow colour) in dairy products as observed in the FFWMP powder samples have previously been associated with β-carotene content [18], which has been linked with dairy products produced from pasture [28].…”
Section: Milk Powder Colour Analysissupporting
confidence: 67%
“…The a* values were negative across all samples with significantly (p ≤ 0.001) higher values observed for SMP than FFWMP and IMF samples across all treatments with the highest a* value observed in the SMP stored at 37 • C (-5.83). As expected, significantly (p ≤ 0.001) higher b* (yellowness) values were observed in FFWMP samples, due to the increased fat content [27]. Increased b* values (blue-to-yellow colour) in dairy products as observed in the FFWMP powder samples have previously been associated with β-carotene content [18], which has been linked with dairy products produced from pasture [28].…”
Section: Milk Powder Colour Analysissupporting
confidence: 67%
“…It is usually considered that powders containing particles of more than 200 μm are free‐flowing while fine powders (<100 μm) due to cohesion offer the greater resistance to flow thus affecting the flowability (Kim, Chen, & Pearce, ). In the present study, the particle size were higher than the spray‐dried milk powder varying from 10 to 250 μm (Schuck & Ouest, ), however, lower than the particles of roller‐dried powder (108.89–168.14 μm) as reported by Pugliese et al (). This may be due to the dependency of particles shape and size on drying systems and further grinding operations.…”
Section: Resultscontrasting
confidence: 48%
“…The color values of milk powders.The brightness value of WMP were found to be as 90.98. Similar findings were reported by Pugliese et al[34] (L*=96.06-96.49, a*= (-)1.78-(-)1.43, b*=13.70-14.59 for whole milk powder. The oxidation or browning reaction may be prevented during the spray drying due to the antioxidant activity of the CNP and GP.…”
supporting
confidence: 90%
“…The bulk and tapped density values of the WMP were found to be as 216.92±8.79 kg/m 3 and 442.50±11.59 kg/m 3 . Pugliese et al [34] reported that the bulk and tapped density values of the spray-dried four whole and seven skim milk powders varied between 396-480kg/m 3 and 553-662kg/m 3 and 407-666kg/m 3 and 578-87kg/m 3 , respectively. The different density values may be due to the different process conditions (inlet/outlet temperature, feed flow rate, atomization pressure etc.)…”
Section: Powder Properties Of Milk Powders and Agglomeratesmentioning
confidence: 99%